An External Command Reading White line Follower Robot (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The report discusses the design of an 8051 based white line follower robot which acceptsthe commands placed along the white line and reacts accordingly. White line follower robot is anautonomous robot which once placed on a white line keeps following it. It makes use of LDRs todistinguish between contrasting light and dark coloured surfaces (in this case it is white colouredline in form of a strip over a black surface). These kind of robots find applications in manysituations like in places where some materials are to be transferred from one place to another.They carry out the navigation task without human guidance as they are able to sense where tomove by following the white line. This report describes a novel mechanism by which thebehavior of line following robots can be altered and controlled by using external commands.These commands are themselves a pattern of white strips which are kept along the white linepath of robot. Upon reading these commands robot carries out necessary actions like slowingdown, turning left in next junction etc. These commands allow us to have more control on therobot and thus improves the usability. The code is written is C language using Keil as the IDEand debugger. The status of the robot while following line and accepting commands wasdisplayed using status LEDs. The Robot was found to follow the path and take the turnsaccordingly along with executing the commands kept on the track.